TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI KAMBING DENGAN SISTEM JOGROK DI DESA BUMI JAWA-BATANGHARI NUBAN-LAMPUNG TIMUR - Pangestuti, Dian Indah (Jurnal Ekonomi Syariah Darussalam, 2024)
Trading goat in Bumi Jawa village using the jogrok system involves bulk transactions where all goats, typically between 30 and 50, are sold at an estimated price. Therefore, this issue warrants investigation to understand why the farmers in Bumi Jawa Village prefer this transaction model and how the validity of bulk goat trading under the jogrok system is viewed from the perspective of Islamic law. This study is field research conducted in Bumi Jawa Village using a normative-empirical approach. The findings indicate that the practice of bulk goat trading using the jogrok system is favored by both farmers and buyers because it is more efficient in terms of time and effort and more profitable. According to Islamic law, this practice falls under the category of jizaf transactions and is permissible because it meets the legitimate requirements of jizaf transactions. Concerning the element of gharar (uncertainty) it falls into the category of permissible gharar by consensus of scholars, as the level of gharar is minor and difficult to avoid.